2012
DOI: 10.1186/1472-6882-12-s1-p242
|View full text |Cite
|
Sign up to set email alerts
|

P02.186. CAST (Centella asiatica selected triterpenes): stability, safety, and effect on diabetic neuropathy (DN)

Abstract: The Ayurvedic nerve tonic herb Centella asiatica demonstrates potential neuro-regenerative properties in in vitro and in vivo models. The aims of the present study were to evaluate the safety and therapeutic effects of CAST (Indena ® , Milan, Italy) in humans with DN, while monitoring the stability of CAST during the trial period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The dynamic properties of the cell cortex and its actin cytoskeleton determine important aspects of cell behavior and are a major target of cell regulation. The expression of Marcks has been found to be locally abundant and to correlate with morpho-genic processes and cell motility, and the protein accumulates at plasmalemmal rafts, where it is co-distributed with PI( 4 , 5 ) P( 2 ) and promotes its retention and clustering ( 25 ). DN is the most common cause of end-stage renal disease (ESRD) among type 2 diabetes mellitus patients (DM) in Malaysia ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic properties of the cell cortex and its actin cytoskeleton determine important aspects of cell behavior and are a major target of cell regulation. The expression of Marcks has been found to be locally abundant and to correlate with morpho-genic processes and cell motility, and the protein accumulates at plasmalemmal rafts, where it is co-distributed with PI( 4 , 5 ) P( 2 ) and promotes its retention and clustering ( 25 ). DN is the most common cause of end-stage renal disease (ESRD) among type 2 diabetes mellitus patients (DM) in Malaysia ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The accurate and timely detection, characterization and quantification of DN are critical for the identification of patients at risk, the estimation of expected deterioration, the monitoring of progression, the assessment of novel therapies, and, ultimately, for the reduction of the incidence and cost of treatment for this disease. Current treatments for DN provide symptomatic relief rather than ameliorating disease progression ( 4 ). A previous clinical study on type II diabetes demonstrated that the insulin sensitizer rosiglitazone (Rosi) (Avandia), a synthetic agonist of peroxisome proliferator-activated receptor-γ (PPAR-γ) that is used to improve insulin resistance, is a potential drug for the treatment of DN ( 5 ).…”
Section: Introductionmentioning
confidence: 99%